Evaluation of bleeding following dental extraction in patients on long-term antiplatelet therapy: A clinical trial - K George Varghese; Sudheesh Manoharan; Mohan Sadhanandan (Wolters Kluwer Medknow Publications, 2015)
Objective: The aim of this trial was to evaluate the bleeding after dental extractions among patients on uninterrupted antiplatelet therapy. Materials and Methods: A total of 190 patients under oral antiplatelet drugs requiring extraction of a single molar tooth were randomly assigned to two groups. Group A consisted of 95 patients on uninterrupted antiplatelet therapy and Group B consisted of 95 patients who have discontinued antiplatelet medication 5 days prior to extraction. The bleeding time of all patients was checked prior to extraction. The surgical procedure involved simple extraction of a single molar tooth under local anesthesia. The extraction socket was sutured with 3-0 silk. Pressure pack with gauze was given for 1 h. Bleeding after 1 h, 24 h, 48 h, and 5 days were compared between two groups. Chi-square test was used to compare the variables. P < 0.05 was taken as significant. Results: None of the patients in either group had any significant uncontrollable bleeding after extraction. Conclusion: Hence, we recommend routine single tooth extractions in patients on long-term antiplatelet medication, without interruption or alteration of their medication. Such patients do not have an increased risk of prolonged or excessive postoperative bleeding.